The Impact of COVID-19 Pandemic on the Epidemiology of Hip and Knee Arthroplasty: A Two-Year Look into the Pandemic from A Single Tertiary Referral General Hospital in Indonesia - Hanif, Hanan; Wardhani, Indrayuni Lukitra; Widhiyanto, Lukas; Chilmi, Mohammad Zaim (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2024)
Highlights: Arthroplasty surgeries were reduced significantly during the COVID-19 pandemic. The number of operations gradually increased between the first and second year of the pandemic. Patients' median age and hospital stays were reduced during the pandemic.   Abstract Introduction: The COVID-19 pandemic has had significant effects on arthroplasty surgeries worldwide. Various studies have described decreased arthroplasty procedures among the most common orthopedic surgeries. This study aimed to analyze the effects of the pandemic on the epidemiology and demography of hip and knee arthroplasty in a tertiary referral general hospital in Indonesia. Methods: This was a retrospective study of medical records data conducted on hip and knee arthroplasty cases from the pre-pandemic (April 2019–March 2020), first-year pandemic (April 2020–March 2021), and second-year pandemic (April 2021–March 2022) periods. Each period was compared for epidemiology and demography data, which included the annual number of arthroplasties, female-to-male ratio, age, duration of hospitalization, and in-hospital post-operative rehabilitation participation. All statistical data calculations were performed using the International Business Machines Corporation (IBM) Statistical Package for Social Sciences (SPSS) version 26. Results: This study observed a statistically significant decrease of 232.00% for hip and 371.43% for knee arthroplasty performed during the first-year pandemic and an increase of 41.86% for hip and 74.07% for knee arthroplasty in the second-year pandemic. A decrease in median age and fluctuation of the female-to-male ratio were observed. The median duration of hospitalization was 80.00% shorter between the pre-pandemic and first-year pandemics and 11.11% shorter between the first and second-year pandemics. Participation in rehabilitation fluctuated during each period. There were four positive cases of COVID-19 and two cases of mortality during the first- and second-year pandemics. Conclusion: The COVID-19 pandemic caused a significant reduction in arthroplasties performed during the first year and a slight increase during the second year. Several changes to the demographics of the patients were also observed between the pre-pandemic and the pandemic periods.